The Role Of Pedagogical Technology In Teaching Students Using The Problem Situation Method (Journal of Pedagogical Inventions and Practices, 2024)
This article discusses the problematic approach of pedagogical technology in teaching physics in higher education, the introduction of an innovative approach in lectures, laboratory and practical classes, the brainstorming method in problematic lectures. The causes of the situation, as well as actions and solutions to overcome the problem are given in the table.